2010
DOI: 10.3152/030234210x508633
|View full text |Cite
|
Sign up to set email alerts
|

EU–US differences in the size of R&D intensive firms: do they explain the overall R&D intensity gap?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…On the one hand, some scholars have argued that the lower European R&D spending is mainly due to the so-called structural composition effect and have provided evidence supporting their thesis. This sectoral composition effect arises because the R&D-intensive manufacturing and R&D-intensive service sectors are under-represented in the European economy in comparison to the US (European Commission, 2007;Mathieu and van Pottelsberghe de la Potterie, 2008;Lindmark et al, 2010;Ortega-Argilés and Brandsma, 2010). This view therefore treats the differences in R&D spending rather as an artifact of differences in sector composition.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, some scholars have argued that the lower European R&D spending is mainly due to the so-called structural composition effect and have provided evidence supporting their thesis. This sectoral composition effect arises because the R&D-intensive manufacturing and R&D-intensive service sectors are under-represented in the European economy in comparison to the US (European Commission, 2007;Mathieu and van Pottelsberghe de la Potterie, 2008;Lindmark et al, 2010;Ortega-Argilés and Brandsma, 2010). This view therefore treats the differences in R&D spending rather as an artifact of differences in sector composition.…”
Section: Introductionmentioning
confidence: 99%
“…Both approaches suggested that new knowledge was a key feature of economic performance, but the relationships between knowledge, innovation and firm types were for the first time examined empirically. These empirical approaches represented a major potential breakthrough because while, on the one hand, theoretical arguments from the international business literature suggested that large firms were systematically more likely to be more innovative than other firm types, on the other hand, some Schumpeterian arguments tended to point to the advantages afforded to small firms (Ortega‐Argilés et al, 2009; Ortega‐Argilés and Brandsma, 2010). Yet, without comprehensive data and testing, the debate could not be satisfactorily resolved either way.…”
Section: Evolutions In Our Understanding Of Innovationmentioning
confidence: 99%
“…Insufficient investment in R&D is often argued to be a key reason why Europe has lagged over the years behind the US in terms of economic growth (Uppenberg, 2009), and many scholars argue that the European delay in terms of private R&D investment is mainly due to a sectoral composition effect . This sectoral composition effect arises because the ICT sectors, and the R&D‐intensive manufacturing and R&D‐intensive service sectors are under‐represented in the European economy in comparison with the US (European Commission, 2007a; Mathieu and van Pottelsberghe de la Potterie, 2008; Lindmark et al , 2010; Ortega‐Argilés and Brandsma, 2010). As such, this argument implies that any potential productivity gains associated with new technological advancements will proportionately have a lower impact on the EU than the US economy.…”
Section: The Randd–ict Intensity Gapmentioning
confidence: 99%
“…However, these impacts are not necessarily related to large firms. Using data from the EU R&D Scoreboard, Ortega‐Argilés and Brandsma (2010) run a micro‐econometric analysis the characteristics of the R&D intensity of firms. Their findings suggest that the higher level of R&D intensity in the US with respect to the EU is mainly due to the greater role that high‐R&D intensive small and medium enterprises (SMEs) play in explaining the R&D intensity in US in comparison with the EU.…”
Section: The Randd–ict Intensity Gapmentioning
confidence: 99%